Analisis kualitatif kandungan senyawa polifenol pada daun herba kitolod (Hippobroma longiflora (L.) G.Don) dan potensi pemanfaatannya sebagai sumber polifenol alami - Awaly Ilham Dewantoro; Selly Harnesa Putri; Efri Mardawati (AGROINTEK, 2022)
As the most significant secondary metabolites in plants with various beneficial properties, polyphenols have an increased demand for industrial use. These issues prompted various exploratory studies on various plants to be utilized as natural polyphenols sources. Kitolod (Hippobroma longiflora (L.) G.Don) has the potential to be utilized as natural polyphenols source because of the abundant amount in nature as weed and is known as a traditional herb based on ethnobotanical studies. This study aims to investigate optimal potential utilization by identifying the polyphenols content on kitolod leaves. Identification was carried out by deploying HPLC qualitative analysis methods to specifically evaluate polyphenols content in kitolod leaves. The results showed kitolod leaves contain 14 polyphenols compounds and consist of phenolic acids (gallic acid, caffeic acid, and ferulic acid), flavonoids (catechin, gallocatechin, epigallocatechin,  gallocatechin gallate, epicatechin gallate, myricetin, quercitrin, pelargonidin, baicalin, and diosmin), and another polyphenols groups (ellagic acid). Contained polyphenolic compounds in kitolod leaves can be utilized optimally as natural polyphenols in various industries such as in food, cosmetics and pharmaceutical, pulp and paper, dyes, textiles, biomaterials, and utilized as additional compounds in wastewater treatment.